Formulation development of a live attenuated human rotavirus (RV3-BB) vaccine candidate for use in low- and middle-income countries. Issue 7 (3rd July 2021) - Kumar, Prashant; Shukla, Ravi S.; Patel, Ashaben; Pullagurla, Swathi R.; Bird, Christopher; Ogun, Oluwadara; Kumru, Ozan S.; Hamidi, Ahd; Hoeksema, Femke; Yallop, Christopher; Bines, Julie E.; Joshi, Sangeeta B.; et al.
ABSTRACT: Formulation development was performed with the live, attenuated, human neonatal rotavirus vaccine candidate (RV3-BB) with three main objectives to facilitate use in low- and middle- income countries including (1) a liquid, 2–8°C stable vaccine, (2) no necessity for pre-neutralization of gastric acid prior to oral administration of a small-volume dose, and (3) a low-cost vaccine dosage form. Implementation of a high-throughput RT-qPCR viral infectivity assay for RV3-BB, which correlated well with traditional FFA assays in terms of monitoring RV3-BB stability profiles, enabled more rapid and comprehensive formulation development studies. A wide variety of different classes and types of pharmaceutical excipients were screened for their ability to stabilize RV3-BB during exposure to elevated temperatures, freeze-thaw and agitation stresses. Sucrose (50–60% w/v), PEG-3350, and a solution pH of 7.8 were selected as promising stabilizers. Using a combination of an in vitro gastric digestion model (to mimic oral delivery conditions) and accelerated storage stability studies, several buffering agents (e.g., succinate, adipate and acetate at ~200 to 400 mM) were shown to protect RV3-BB under acidic conditions, and at the same time, minimize virus destabilization during storage. Several optimized RV3-BB candidate formulations were identified based on negligible viral infectivity losses during storage at 2–8°C and −20°C for up to 12 months, as well as by relative stability comparisons at 15°C and 25°C (up to 12 and 3 months, respectively). These RV3-BB stability results are discussed in the context of stability profiles of other rotavirus serotypes as well as future RV3-BB formulation development activities.